Overview of the Trinidad and Tobago economy in 1990 and 1991 and prospects for the future. - Bourne, Compton (1992)
Reviews economic development in Trinidad and Tobago in the two years. Points out that there are now signs of economic recovery, although the outlook for 1992 is dominated by the foreign sector and by developments in the public sector.